Social Media and Financial News Manipulation - Kogan, Shimon; Moskowitz, Tobias J; Niessner, Marina (Review of Finance, 2023)
Abstract We examine an undercover Securities and Exchange Commission (SEC) investigation into the manipulation of financial news on social media. While fraudulent news had a direct positive impact on retail trading and prices, revelation of the fraud by the SEC announcement resulted in significantly lower retail trading volume on all news, including legitimate news, on these platforms. For small firms, volume declined by 23.5% and price volatility dropped by 1.3%. We find evidence consistent with concerns of fraud causing the decline in trading activity and price volatility, which we interpret through the lens of social capital, and attempt to rule out alternative explanations. The results highlight the indirect consequences of fraud and its spillover effects that reduce the social network’s impact on information dissemination, especially for small, opaque firms.